ADCP instrument status from ROV survey PS122/2_18-89 on 2020-01-04, survey 1 - Philipp Anhaus; Christian Katlein; Ilkka Matero; Marcel Nicolaus; Stefanie Arndt; Daniela Krampe; Benjamin Allen Lange; Julia Regnery; Jan Rohde; Martin Schiller (PANGAEA, 2023)
Instrument status from the Nortek Aquadopp Profiler 2MHz acoustic doppler current profiler (ADCP) attached to the remotely operated vehicle (ROV) during the MOSAiC expedition 2019/20.
In: Anhaus, P et al. (2023): Water/ice velocity from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.953510